Gene expression analysis in MCF-7 breast cancer cells treated with recombinant bromelain - Fouz, Nour; Amid, Azura; Hashim, Yumi Zuhanis Has-Yun (Springer, 2014)
The contributing molecular pathways underlying the pathogenesis of breast cancer need to be better characterized. The principle of our study was to better understand the genetic mechanism of oncogenesis for human breast cancer and to discover new possible tumor markers of use in clinical practice. We used cDNA microarrays to compare gene expression profiles of treated MCF-7 with recombinant bromelain and untreated MCF-7. SpringGene analysis was carried out of differential expression followed by Ingenuity Pathway Analysis (IPA), to understand the underlying consequence in developing disease and disorders. We identified 1102 known genes differentially expressed to a significant degree (p<0.001) changed between the treatment. Within this gene set, 17 genes were significantly changed between treated cells and the control cells with cutoff fold change more than 1.5. These genes are RBMS1, RPL29, GSTM2, C15orf32, AKT3, BTG1, C6orf62, C7orf60, KIFAP3, FBXO11, ARID4A, COPS2, TBPL1|SLC2A12, TMEM59, SNORD46, GLTSCR2 and LRRFIP. Our observation on gene expression indicated that recombinant bromelain produces a unique signature affecting different pathways, specific for each congener. The microarray results give a molecular mechanistic insight and functional effects, following recombinant bromelain treatment. The extent of changes in genes related to involved significantly in Gap Junction Signaling, Amyloid processing, Cell Cycle Regulation by BTG Family Proteins and Breast Cancer Regulation by Stathmin1 that play major roles.